An association between average daily sleep duration and gallstones in US adults - Fang, Yong; Xu, Qiuyuan; Xu, Jia; Wang, HaiHua (Scientific reports, 2025)
Despite extensive research on the impact of health factors and sleep, the specific association between average daily sleep duration and the prevalence of gallstones in adults has not been thoroughly investigated. This study analyzes data from 7,441 individuals from the NHANES 2017–2020 dataset, using exclusion criteria to refine the participant pool. Employing multivariate logistic regression and subgroup analyses while controlling for potential confounders, we assessed the association between average daily sleep duration and the prevalence of gallstones. Our results revealed a statistically significant inverse association (OR = 0.92; 95% CI: 0.86, 0.99; p = 0.0236). This association was consistent across various demographic and health-related subgroups. Interestingly, the inflection points were observed among middle-aged adults (40–60 years) and individuals with diabetes. These findings could inform public health strategies on sleep management, potentially aiding in the prevention of gallstones within these populations.